The impact of the key audit matters (KAMS) disclosures on investor’s decision making / Norazura Masdor and Amanuddin Shamsuddin - Masdor, Norazura; Shamsuddin, Amanuddin (UiTM Cawangan Johor, 2019)
In 2015, Malaysia implemented the ISA701 - Communicating Key Audit Matters (KAMs) in the Independent Auditor’s Report to the Malaysian Public Listed Companies (PLCs). The Standard was first observed for audits of financial statements for financial periods ending on or after Dec 15, 2016. Thus, this paper examined the impact of KAMs disclosure on investors’ decision-making. This study explored whether this new requirement is associated with an increase in the investors’ decision usefulness based on the auditor’s report. This study employed critical content analysis on the samples that consisted of 337 PLCs in Bursa Malaysia for the year ended December 2016. Share prices were used as dependent variables to represent investors’ responsiveness when KAMs disclosed in audit reports. The share prices cover three periods of analysis; average seven days before event date (audit report date), at event date, and average seven days after event date. Independent variables include KAMs and control variables are profitability, leverage and size. Findings from the study suggest that the mandating of KAM’s disclosure has no informational value to the investors of Malaysian PLCs. Nevertheless, the paper did not offer a comprehensive analysis of KAMs issues; rather it focused on the impact of KAMs disclosure on investors’ reaction on the first year of implementation. However, the paper encourages reflections on contemporary practices and offers some suggestions for reform in the near future.